Functional Properties of Campomanesia xanthocarpa Infusions: Phenolic Profile, Digestive Stability, Enzyme Inhibition, and Glycemic Effects - Cristiane Maria Chitolina Tremea; Vanessa Ruana Ferreira da Silva; Larissa Cunico; Vinícius Gottardo Boff; Carolina Turnes Pasini Deolindo; Aleksandro Shafer da Silva; Aniela Pinto Kempka (Foods)
This study investigated the functional potential of Campomanesia xanthocarpa leaf and fruit infusions through phytochemical profiling, simulated gastrointestinal digestion, enzyme inhibition assays, and in vivo evaluation of glycemic markers. Leaf infusions exhibited a more diverse phenolic profile, higher total phenolic content, and greater antioxidant capacity compared to fruit infusions. Simulated digestion confirmed the bioaccessibility of key phenolic compounds, particularly glycosylated flavonoids such as quercetin-3-glucoside and kaempferol derivatives, with leaf extracts showing superior gastrointestinal stability. In vitro assays revealed a strong inhibitory activity of leaf infusions against α-amylase and β-glucosidase. In a 32-day trial with healthy dogs, the consumption of biscuits enriched with leaf infusion did not alter fasting glucose or amylase levels but resulted in a significant treatment × time interaction for serum fructosamine, indicating a delayed modulation of glycemic control, potentially associated with antioxidant or anti-glycation activity. These findings highlight the potential of C. xanthocarpa leaves as a functional ingredient in foods aimed at supporting glycemic regulation and metabolic health.